Sneddon syndrome a case report and literature review - Leon, Rafael R. P.; Sánchez, Iliana N. C.; Reyes, Jorge A. P.; Valdez, Luis F. D.; Romero, Luis F. A.; Corona, Carlos U. C.; Lopez, Diana K. S.; Chavez, Marcos O. M.; Melgarejo, Ivan A. S.; Vivanco, Marlene I. M. (International Journal of Research in Medical Sciences, 2022)
Sneddon’s syndrome (SS) is characterized by livedo racemosa (LR) or reticularis and recurrent ischemic strokes. At the skin and brain level a non-inflammatory thrombotic vasculopathy is observed. Almost 80% of cases are women around 40 years old. The most accepted etiological proposal is an autoimmune and inflammatory mechanism versus the presence of thrombophilia. Neurological manifestations occur in 3 phases: prodromal symptoms (headache, dizziness, and vertigo), recurrent strokes, and early-onset dementia. Livedo racemosa has been reported to precede strokes by more than 10 years. Treatment is mainly based on secondary prophylaxis preventing a stroke with antiplatelet and antithrombotic agents. The neuropsychiatric prognosis is relatively poor with deficits in concentration, attention, visual perception, and visuospatial skills.